The association between triglyceride-glucose index and gallstones: NHANES 2017-2020 - Gong, Li; Fan, Shujin; Peng, Zhenfei; Chen, Zeyao; Liu, Yuzhou; Huang, Yinluan; Wang, Chaofan; Piao, Chunli (Frontiers in Endocrinology, 2024)
Objects: It remains unclear whether the triglyceride-glucose (TyG) index has correlations with gallstones. This study aimed to investigate the association between TyG index and gallstones. Methods: Data was obtained from the 2017-2020 National Health and Nutrition Examination Survey (NHANES). Participants who provided complete data about TyG index and gallstones were included in the analysis. Multivariable regression analysis and subgroup analysis were preformed to estimate the relationship between TyG index and gallstones. Restricted cubic splines (RSC) was employed to calculate the cut off value. Results: The TyG index was independently associated with gallstones and demonstrates a clear positive correlation (OR = 1.10; 95% CI: 1.01–1.21; p = 0.033). The threshold value is 8.98, showing a positive correlation between TyG index and gallstones when the TyG index is less than 8.98 (Log likelihood ratio P < 0.001). Subgroup analysis indicates that the correlation between TyG and gallstones is mainly observed in individuals with obesity, females, younger individuals, and those with normal blood sugar levels, with these subgroups all acting as mediators between TyG and gallstones. Conclusions: Higher TyG index was linked to a higher chance of developing gallstones. Managing insulin resistance (IR) could help reduce the risk of gallstones since the TyG index is an indicator of IR.